Trajectory tracking with time-varying terrain conditions for an autonomous omnidirectional mobile robot using stratified variable structure saturated control. Issue 5 (3rd April 2020) - Hwang, Chih-Lyang; Lee, Yunta; Hung, Wei-Hsuan
ABSTRACT: The trajectory tracking model of an autonomous omnidirectional mobile robot (ODMR) with different friction model for each wheel and motor dynamics is first achieved. Due to the fully actuated feature, the reference pose for ODMR is easily planned as compared with the under-actuated mobile robots. Subsequently, the reference motor current (RMC) is designed by the first switching surface. To make the motor current asymptotically track the RMC, a variable structure tracking control (VSTC) with the saturated output is designed by the second switching surface. The consideration of motor dynamics is to deal with the high-frequency motion behaviours of trajectory tracking, e.g. time-varying terrain, inaccurate friction model, discontinuous reference pose. The larger roughness of time-varying terrain, discontinuity of the reference pose or inaccurate friction model, the larger high-frequency amplitude of control input. In summary, the proposed stratified variable structure saturated control (SVSSC) includes the RMC and VSTC with the saturated output. The simulations for the circular trajectory with different nominal friction force and torque of each wheel and uncertainties by the SVSSC are satisfactorily achieved. The corresponding experiments with the mat on the reference trajectory and different reference pose for ODMR validate the effectiveness, robustness, and practicality of the proposed control.